Strategi pemenangan dalam pemilihan kepala daerah - Bowo Sugiarto; Oktafiani C Pratiwi; Andi A Said Akbar (Faculty of Social and Political Science, Universitas Airlangga, 2014)
Based on empirical case of Husein and Budhi‟s victory in the Banyumas local election in 2013, this article gives contribution to the study of political communication, especially on the issue of the campaign. The context of this article is the incumbent head of regency candidate, who had more chances to win, was defeated by the other candidate. The research method used was descriptive qualitative. This research was conducted in Banyumas. The data collected by interview and informant were chosen by purposive sampling technique. The aim of this research is to report Husein-Budhi campaign team and political party members. This article includes analysis of the Husein and Budhi‟s strategy to win the local election and the contextual factor supported their winning. Those strategies encompass areas of party consolidation, segmentation, targeting, positioning, and .the image of candidate Those strategies are the creation of images that he is not part of the incumbents so he cannot be in charged by any criticism to the local government, the campaign issues that correspond with the weakness of the potential rival and the campaign objectives, the party rooting by involving elements of civil society and the party consolidation which is included from the candidacy process to campaign by employing local legislative candidates. The contextual factor is the information about the potential rival candidate‟s weakness that caused voters' disappointment to him. In conclusion, the future head of regency can win an election by doing the same strategy as Husein-Budhi.